Du crime passionnel au féminicide. À propos de l’affaire Chambige - Aya Umezawa (Criminocorpus)
This article takes the opportunity of Jacqueline Carroy and Marc Renneville's exhumation of the Chambige affair to look at Chambige's friends. In their discourse, Chambige is the victim of a thirty-year-old woman, and this woman, dead, is a guilty mother. The term 'crime passionnel', coined at the same time, also potentially justified the author. In the twentieth century, De Greeff denounced the hatred of women that hides behind compassion for criminals of passion, and Bourdieu pointed out that men's brutality originates in an anguish towards women. In the nineteenth century, the word 'femicide' was increasingly used to take the victim's perspective. However, there is a persistent tendency to look for reasons in the person who kills a woman and for faults in the victim: from this point of view, the 19th century case still seems to be relevant.